Effect of Vacuum Packaging on Physical Properties of Kesar Mango - Antala, D K; Sangani, V P; Bhatt, V M; Vyas, D M; Varshney, A K (Journal of Agricultural Engineering, 2006)
The freshly harvested mango (Kesar) fruits were packed in 100 gauge Polyethylene bags at 700, 600 and 500 mm Hg vacuum and stored at 13 ± 2degree C, 18 ± 2degree C and room temperature (36 ± 3degree C), Results revealed that vacuum packaging and storage temperature had significant effect on physical and mechanical properties of the mango fruits. It was observed that physiological weight loss and pulp/peel ratio increased with storage period while firmness, specific gravity and mechanical strength decreased. Vacuum packed fruits stored at 13 ± 2degree C, increased storage life up to 44 days with minimum changes on physical and mechanical properties of the fruits.